Link between TLR4/MyD88/NF-κB levels, inflammation, and infectious preterm birth in pregnant women - Wang, Meixia; Wang, Xiaofang; Deng, Haiyun; Liu, Xue; Xv, Min (Medicine (Baltimore), 2025)
Infectious preterm delivery is a serious health problem in pregnant women. The pathogenesis of infectious preterm delivery is associated with the alterations of Toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor κB (NF-κB) and other inflammatory factors. This study investigates the correlation of TLR4/MyD88/NF-κB and inflammatory factors with infectious preterm labor in pregnant women. A total of 200 preterm delivery parturients admitted to our hospital were retrospectively selected as research subjects, including 100 infected preterm delivery parturients (infected group) and 100 noninfected preterm delivery parturients (noninfected group), while the control group included 100 normal full-term parturients. In order to analyze the clinical value of these indexes in predicting infectious preterm delivery, a receiver operating characteristic curve was used. The levels of TLR4/MyD88/NF-κB, interleukin-1β, C-reactive protein, tumor necrosis factor-α (TNF-α), and interleukin-6 in infected group were significantly higher than those in noninfected group and control group (P < .05). Based on receiver operating characteristic curve analysis, it was found that the area under curve of TLR4/MyD88/NF-κB for diagnosing infectious preterm delivery were 0.771, 0.846, and 0.789, respectively. Changes in interleukin-6 levels and TLR4/MyD88/NF-κB may reflect the risk of infectious preterm delivery in pregnant women to some extent.